The effectiveness of using a mobile messenger as an educational supporting tool among nursing students - Rohimah, Ismail; Hasnah, Zani; Zainab, Mohd Shafie (Penerbit Universiti Sultan Zainal Abidin, 2020)
The evolution of information technology has exerted great influence on nursing education via new pedagogy of knowledge delivery without time and place restriction. Mobile technology revolutionises nursing education and clinical practice via empowering skills of critical thinking and clinical decision-making through learning. The aim of this study is to evaluate the effectiveness of using mobile messenger (Whatsapp) as an educational supporting tool among nursing students. The study design used is a Cluster Randomized Control Trail. Two nursing colleges were selected. Sample size was 93 participants, 48 from the Kuala Terengganu Nursing College Kuala Terengganu as the intervention group while the control group were recruited among 45 participants from UniSZA Nursing College. There is a significant difference in the level of knowledge between pre and posttest among intervention group (mean difference was -8.70 with a standard deviation 8.42, p-value< 0.001) and 93.8 percent of the respondents perceived the usefulness of using WhatsApp mobile messenger to enhance learning. This demonstrates that learning through mobile messenger (WhatsApp) enhances learning and is well received as a new method of learning by almost all students.